Knowledge, attitude, and practices of surgeons regarding venous thromboembolism prophylaxis in tertiary healthcare hospitals of the Rawalpindi Districts - Amna Khan; Syeda Fatima; Aamna Abbas Naqvi (Journal of the Pakistan Medical Association)
Objectives: To assess doctors' knowledge, attitudes and practices regarding venous thromboembolism prophylaxis.